2009
DOI: 10.1242/jeb.025536
|View full text |Cite
|
Sign up to set email alerts
|

The numerical comparison of flow patterns and propulsive performances for the hydromedusaeSarsia tubulosaandAequorea victoria

Abstract: SUMMARYThe thrust-generating mechanism of a prolate hydromedusa Sarsia tubulosa and an oblate hydromedusa Aequorea victoria was investigated by solving the incompressible Navier-Stokes equations in the swirl-free cylindrical coordinates. The calculations clearly show the vortex dynamics related to the thrust-generating mechanism, which is very important for understanding the underlying propulsion mechanism. The calculations for the prolate jetting hydromedusa S. tubulosa indicate the formation of a single star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
73
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 31 publications
4
73
0
1
Order By: Relevance
“…Recent work using digital particle image velocimetry (DPIV) and computational fluid dynamics has elucidated the mechanisms by which jellyfish effectively propel themselves and feed. The specific details on the relationship between unsteady fluid dynamics and swimming efficiency have been investigated using mathematical modeling (Daniel, 1983;Daniel, 1984;Dabiri et al, 2007), experiments (Costello and Colin, 1994;McHenry and Jed, 2003;Dabiri et al, 2005) and numerical simulations (Sahin et al, 2009;Lipinski and Mohseni, 2009). More recent studies have used DPIV and Lagrangian coherent structures (LCS) to characterize the vortex shedding and fluid mixing due to the pulsations of the bell (Dabiri et al, 2010;Peng and Dabiri, 2008a;Peng and Dabiri, 2008b;Peng and Dabiri, 2009;Lipinski and Mohseni, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work using digital particle image velocimetry (DPIV) and computational fluid dynamics has elucidated the mechanisms by which jellyfish effectively propel themselves and feed. The specific details on the relationship between unsteady fluid dynamics and swimming efficiency have been investigated using mathematical modeling (Daniel, 1983;Daniel, 1984;Dabiri et al, 2007), experiments (Costello and Colin, 1994;McHenry and Jed, 2003;Dabiri et al, 2005) and numerical simulations (Sahin et al, 2009;Lipinski and Mohseni, 2009). More recent studies have used DPIV and Lagrangian coherent structures (LCS) to characterize the vortex shedding and fluid mixing due to the pulsations of the bell (Dabiri et al, 2010;Peng and Dabiri, 2008a;Peng and Dabiri, 2008b;Peng and Dabiri, 2009;Lipinski and Mohseni, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Jellyfish have been the subject of vigorous biomechanical and fluid dynamic research aimed at understanding the nature of unsteady propulsion (Dabiri, 2005;Dabiri et al, 2007;Daniel, 1985;Daniel, 1995;Demont and Gosline, 1988;Lipinski and Mohseni, 2009;Rudolf, 2007;Sahin et al, 2009). Demont and Gosline (Demont and Gosline, 1988) and Daniel (Daniel, 1985) showed that the bell is driven at its resonant frequency, which increases the efficiency of this form of unsteady locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…Demont and Gosline (Demont and Gosline, 1988) and Daniel (Daniel, 1985) showed that the bell is driven at its resonant frequency, which increases the efficiency of this form of unsteady locomotion. More recent studies have used digital particle image velocimetry (dPIV) and Lagrangian coherent structures to characterize the vortex shedding, mixing and particle capture associated with jellyfish locomotion (Dabiri, 2008;Dabiri et al, 2010;Peng and Dabiri, 2008a;Peng and Dabiri, 2008b;Peng and Dabiri, 2009;Sahin et al, 2009). Rudolf used immersed boundary methods to develop animations of swimming jellyfish (Rudolf, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For both swimming modes, contraction of the bell by subumbrellar muscles expels fluid from the subumbrellar cavity and creates a starting vortex (Dabiri et al, 2005). During relaxation of the same subumbrellar muscles, fluid is brought into the subumbrellar cavity as a result of a drop in internal pressure, and creates a stopping vortex (Dabiri et al, 2005;Sahin et al, 2009). Rowing propulsion is characterized by strong interactions between these stopping and starting vortices to achieve a propulsive advantage (Dabiri et al, 2005).…”
Section: Introductionmentioning
confidence: 99%